Influence Online Learning During a Pandemic at the Understanding Level of Mathematics Lessons Elementary Students - Sindu Arif Rizai; moh. zainudin; Eka Nurjanah (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Covid-19 pandemic that happened at the start 2019 gives _ outside impact _ common to all sector . it _ impact on activities learn finally _ done online (online). Mathematics is long lessons _ This feared by students , though so online learning has effect positive and negative . In implementation this online learning there is Lots problems encountered in the field . Study This use method study qualitative with study history and studies case . Studies case conducted on students of SDN Selorejo 1 District Kawedanan Regency Magetan . In the 1st semester of the year teaching 2022/2023. Objective study This is For know influence online learning against level understanding lesson mathematics in students school basic . Many problems encountered _ in online learning mainly in lessons math , fine from student internal factors nor factor external student . Basically _ what the teacher conveys in online learning , no Can accepted completely by students .